Determinación de la concentración de nutrientes N, P, K en los residuos sólidos orgánicos selectivos provenientes del mercado Ayaymaman, mediante la técnica del compostaje - Mansilla Dela Peña, Marco Antonio (2013)
The research project, Determination of the concentration of nutrients N, P, K in selective organic solid waste from Ayaymaman market using the technique of composting, specific aims: Perform classification Generation Sectors Organic Solid Waste, Ayaymaman Market Moyobamba ~ity; build processing Composting for Organic Solid Waste; determine the concentrations of N, P, K, pH, electrical conductivity and organic matter contained in the compost. The problem statement was: What is the concentration of nutrients in selective organic solid waste, from Ayaymaman market? The variables were: lndependent Variable, Xi: Fields of study. And dependent variable Yi: concentration of nutrients N, P, K, EC, pH and organic matter. The hypothesis to prove, If, elaborate compost Organic Solid Waste selective Ayaymaman from the market, then the concentration of nutrients N, P, K are significant. The methodology consisted in requesting authorization to Moyobamba district municipality, in coordination with the market administrator; provide BRIEFING A MARKET TRADERS, collection was made during a week (Sunday - Sunday) discarding the frrst day that is considered as zero-day pickup schedule was from 3 :00 pm. The waste shipment was made on a motorcycle freighter (van), Ecotourism center the "Milan", instead of the built environment ( compost), the weight was a British brand needle scale, up to 40 kg, weighing is performed by components and the volume was determined with a bucket of 45 liters. Density was determined by the volume-"weight ratio. Moisture was determined by The Kiln Drying Method. The chemical analysis of the compost obtained was held at the National University of San Martin, Tarapoto, which method was for N Kjeldahl method modified for P, the colorimeter method for K cremated method. In sectors classification generation of organic waste, Ayaymaman market, classified according to the origin and nature: food industry, fruit and vegetable industry andjuices industry. JR. PROLONGACIÓN 20 DE ABRIL S/N- TELEF. 042· 562458 MOYOBAMBA- PERU Xlll "AÑO DE LA INVERSIÓN PARA EL DESARROLLO-RURAL Y LA. SEGURIDAD-ALIMENTARIA" For .the construction of. the· .compost· for .processing .solid .organic· waste· was used 't}3ambo" (Gua9ua.superba) and·w~od (lumb~r) .. -In . determining . the . con~entrations . of N, -P~ . K, pH~ . or~~ic matter and· containing ·. electricál conductivi~ fmal_ly compost ·formed- from- organic so lid waste Ay~ymaman . . market-was as-·follows